2005
DOI: 10.1007/s10569-005-1783-3
|View full text |Cite
|
Sign up to set email alerts
|

Motion On the Sphere: Integrability and Families of Orbits

Abstract: We study the problem of the motion of a unit mass on the unit sphere S 2 and examine the relation between integrability and certain monoparametric families of orbits.In particular we show that if the potential is compatible with a family of meridians, it is integrable with an integral linear in the velocities, while a family of parallels guarantees integrability with an integral quadratic in the velocities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…These results have been recently obtained by Voyatzi and Ichtiaroglou [17]. The straight lines v = c are geodesics and the circles u = c are orthogonal to them, see Fig.…”
Section: Examplessupporting
confidence: 83%
See 1 more Smart Citation
“…These results have been recently obtained by Voyatzi and Ichtiaroglou [17]. The straight lines v = c are geodesics and the circles u = c are orthogonal to them, see Fig.…”
Section: Examplessupporting
confidence: 83%
“…the angular momentum), while a family of concentric circles guarantees that the potential is separable in polar coordinates and thus possesses an integral, quadratic in the velocities. On the other hand, Voyatzi and Ichtiaroglou [17] studied motion on the two-dimensional sphere and showed that the permissibility of a family of meridians or a family of parallels guarantees integrability, with linear or quadratic integrals respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We also note that our results contain those of [61,64] We emphasize that the potentials listed in Table 4.12 concern dynamical systems with Lagrangian (4.42) which are integrable via Noether point symmetries.…”
Section: Noether Symmetriessupporting
confidence: 59%
“…In fact, it has been studied by many authors (see e.g. [48][49][50][51][52][53][54][55][56][57][58][59] and references therein) mainly in relation of the theory of dynamical symmetries.…”
Section: On the Relation Of This Nonlinear Model With The Harmonic Osmentioning
confidence: 99%